2013
DOI: 10.1002/mawe.201300080
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented impact test of duplex stainless steel miniature specimen

Abstract: The paper describes a new approach to characterize metallic materials by a novel instrumented notch impact test for samples with small specimen size. A piezo‐electric sensor mounted on the pendulum hammer provides force information during the fracture process. By numerical integration of the signal the absorbed impact energy can be calculated very exactly. Further information about the fracture behavior can be extracted from the resulting force‐displacement‐diagram. Several duplex stainless steels in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Charpy impact tests characterize the susceptibility of a material to brittle fracture under dynamic load and quantify the energies absorbed during crack initiation and crack propagation. 53 Polymers having high crack initiation energy but low crack propagation energy in impact exhibit high unnotched impact strength, but low notched impact strength. 54 Crack initiation is the major dissipation mechanism in a number of polymers.…”
Section: Evaluation Of P(3hb) Propertiesmentioning
confidence: 99%
“…Charpy impact tests characterize the susceptibility of a material to brittle fracture under dynamic load and quantify the energies absorbed during crack initiation and crack propagation. 53 Polymers having high crack initiation energy but low crack propagation energy in impact exhibit high unnotched impact strength, but low notched impact strength. 54 Crack initiation is the major dissipation mechanism in a number of polymers.…”
Section: Evaluation Of P(3hb) Propertiesmentioning
confidence: 99%
“…210 Crack propagation velocity can be calculated from the duration of impact and the length of fracture zones. 148…”
Section: Crack Growthmentioning
confidence: 99%
“…19,209 The effect of small punch test machine dimensions was investigated, it was discovered that punch diameter had a significant effect, mainly if it is too small it can cause brittle failure. 25 A possible advantage of small punch Eck and Ardell 97 Small compact tension specimens 159,160,163,[165][166][167]203,206,207 3-point bending specimens 136,137,139,143,146,162,208 Small Charpy specimens 51, 144,147,148,150,163,203 Indentation specimens 100,101,117,119 Bespoke specimens Xinping et al 169 testing, found in one study, could be that the scatter of DBTT values was approximately half of the scatter from Charpy testing. 27 DBTT shift due to helium ions causing irradiation damage was investigated using small punch specimens and it was discovered that there was essentially no effect.…”
Section: Ductile To Brittle Transition Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…A precipitação da fase sigma nos aços inoxidáveis é uma das principais razões para a deterioração das propriedades desses aços, incluindo aqui a resistência mecânica, a resistência à corrosão e a soldabilidade. Wunder et al (2013) analisaram os efeitos da precipitação da fase sigma no aço inoxidável duplex S32003 (DIN 1.4593) usando ensaios de impacto Charpy. Com a transformação de boa parte da ferrita  em fase sigma , através da reação eutetóide ( →  + ), a energia absorvia no ensaio de impacto para o aço inoxidável duplex em questão foi reduzida em 97%.…”
Section: Evolução Metalúrgica Das Juntas Soldadas Com E308l E E316lunclassified